2018
DOI: 10.20452/pamw.4297
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in chronic obstructive pulmonary disease patients. Does cellular senescence matter?

Abstract: Prevention and early detection of lung cancer in patients with chronic obstructive pulmonary disease: screening programs and reducing exposure to risk factors Given that COPD favors carcinogene sis in the respiratory system, there is a need to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Senescent cells have been reported in both human and animal models of pulmonary diseases (2,5,6,41,71,107,158,187). Indeed, given that chronologic age is a major risk factor for most chronic diseases, including COPD, asthma, and PF, there is relevance to identifying senescence as a fundamental aging process that, if targeted appropriately, could impact on disease alleviation and overall health in the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Senescent cells have been reported in both human and animal models of pulmonary diseases (2,5,6,41,71,107,158,187). Indeed, given that chronologic age is a major risk factor for most chronic diseases, including COPD, asthma, and PF, there is relevance to identifying senescence as a fundamental aging process that, if targeted appropriately, could impact on disease alleviation and overall health in the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that cellular senescence actively contributed to age‐related diseases and tumorigenesis via the senescence‐related secretory phenotype 35 . It has been demonstrated that cellular senescence promoted carcinogenesis in patients with chronic obstructive pulmonary disease 36 . Besides, membrane‐bound CD40L contributed to cellular senescence and activated senescence‐associated secretory phenotype in LUAD 37 .…”
Section: Discussionmentioning
confidence: 99%
“… 35 It has been demonstrated that cellular senescence promoted carcinogenesis in patients with chronic obstructive pulmonary disease. 36 Besides, membrane‐bound CD40L contributed to cellular senescence and activated senescence‐associated secretory phenotype in LUAD. 37 However, the correlation between cellular senescence and RAGE expression has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in vitro experiments to better characterize the function of HRG in lung cancer patients, including HRG binding to heparin and fibrin clots [34–36], should be performed in the future. It is also worth investigating whether HRG levels and fibrin properties in lung cancer patients are associated with inflammation and cellular senescence [37].…”
Section: Discussionmentioning
confidence: 99%